Pengaruh Penerapan E-Filing, Sosialisasi Pajak, Tingkat Pemahaman Pajak, Sanksi Pajak Dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi Di Kpp Pratama Surabaya Mulyorejo - Intan Nur Fadilah; Surenggono (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to analyze the effect of the implementation of e-filing, tax socialization, tax understanding level, tax sanctions and taxpayer awareness on the compliance of individual taxpayers at KPP Pratama Surabaya Mulyorejo. Data was collected using a questionnaire distributed to individual taxpayers registered at KPP Pratama Surabaya Mulyorejo. The analysis technique used is multiple linear regression analysis. The results of the study show that the implementation of e-filing, tax socialization and taxpayer awareness have a positive and significant effect on the compliance of individual taxpayers. Meanwhile, the level of tax understanding has a significant negative effect and tax sanctions have no effect on the compliance of individual taxpayers.